2007
DOI: 10.5194/aab-50-155-2007
|View full text |Cite
|
Sign up to set email alerts
|

Milk yield and reproductive performance of Friesian cows under Sudan tropical conditions

Abstract: Abstract. The data obtained from the dairy herd of the Arab Company for Agricultural Production and Processing (ACAPP) in a semi arid area 40 km south of Khartoum involved 337 cows with a total of 1049 records from 16 years between 1986 and 2002. The least squares means for age at first calving, calving interval, days open, lactation milk yield, daily milk yield, lactation length and dry period were 29.76±0.40 months, 433.12 ± 6.70 days, 167.79±7.08 days, 3475.53±78.89 kg, 12.29±0.28 kg, 294.10±3.62 days and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 15 publications
5
14
0
Order By: Relevance
“…Table (3) display the effects of parity, season and year of calving on TMY, 305d-MY LP, NSC and AFC. Mean of TMY for autumn and spring had longer than compared summery (table 3) this results agreement Usman et al (2011) and Abdel-Gader et al, (2007). Averages of 305d-MY were higher for cows calved in winter and autumn than in spring and summer.…”
Section: Resultssupporting
confidence: 88%
“…Table (3) display the effects of parity, season and year of calving on TMY, 305d-MY LP, NSC and AFC. Mean of TMY for autumn and spring had longer than compared summery (table 3) this results agreement Usman et al (2011) and Abdel-Gader et al, (2007). Averages of 305d-MY were higher for cows calved in winter and autumn than in spring and summer.…”
Section: Resultssupporting
confidence: 88%
“…The heritability estimate of CI was very low (0.03). Similar estimates were reported previously [27,33]. However, higher estimates were published by Islam et al [37].…”
Section: Heritability Estimatessupporting
confidence: 92%
“…High heritability estimates for fat and protein yields (0.37 and 0.32, respectively), which are consistent with those obtained by Mashhadi et al [29], but are higher than those recorded by others [30,31]. Days in milk had a medium heritability estimate (0.11), which was similar to those reported previously [32,33]. On the other hand, these estimates were much higher than those reported by Ayied et al [25], but were lower than those recorded by others [5,34].…”
Section: Heritability Estimatessupporting
confidence: 90%
See 1 more Smart Citation
“…However, such detected adverse or undesirable environmental effect during autumn and winter (positive environmental effect) may be due to the lack of green fodders. (Abdel-Gader et al 2007) found that milk production was higher in winter. While he was higher in the spring and autumn seasons and less in the summer due to the weather is hot (Javed et al2004).…”
Section: Fig 2 Env Of Reproductive Traits As Regressed Against Yearmentioning
confidence: 99%